2003
DOI: 10.1002/cbic.200390035
|View full text |Cite
|
Sign up to set email alerts
|

External Regulation of Hairpin Ribozyme Activity by an Oligonucleotide Effector

Abstract: The hairpin ribozyme belongs to the class of self-cleaving nucleases that are found in plant viroids, virussoids or viral satellite RNAs. [1] The 50-nucleotide-long minimal sequence (Figure 1) catalyses the reversible specific cleavage of a suitable 14nucleotide-long RNA substrate. The secondary structure of the Received: September 19, 2002 [Z 491] [a] Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…396,397 Approaches for the direct detection of oligonucleotides without the requirement of any external labeling become increasingly important because they would allow for the analysis and quantification of a nucleic acid in an organism, cell, or tissue which is incompatible with extra chemical steps such as attachment of fluorophores or radioactive residues. 398 One of our aims, therefore, was to design allosteric hairpin ribozyme constructs allowing the direct detection of microRNAs 393 (miRNAs).…”
Section: Aptazymes Based On the Hairpin Ribozymementioning
confidence: 99%
“…396,397 Approaches for the direct detection of oligonucleotides without the requirement of any external labeling become increasingly important because they would allow for the analysis and quantification of a nucleic acid in an organism, cell, or tissue which is incompatible with extra chemical steps such as attachment of fluorophores or radioactive residues. 398 One of our aims, therefore, was to design allosteric hairpin ribozyme constructs allowing the direct detection of microRNAs 393 (miRNAs).…”
Section: Aptazymes Based On the Hairpin Ribozymementioning
confidence: 99%
“…Previously, we have shown that hairpin ribozyme activity can be allosterically controlled by external cofactors. 79,80 Therefore, a possible scenario of hairpin ribozyme supported RNA circularization could exist of enzymatic or chemical synthesis of linear precursors containing the hairpin ribozyme structure at the ligation junction, but requiring an additional cofactor, such as an oligonucleotide effector or an allosteric activator, for induction of ligation. After reaction, the cofactor can be removed, thus switching off hairpin ribozyme activity and leaving behind the ligated RNA as stable circle.…”
Section: Ribozymes For Rna Circularizationmentioning
confidence: 99%
“…These reporter ribozymes join other ribozymes that report nucleic acids. [83][84][85][86] They are entirely RNAbased and thus could be expressed endogenously, requiring only the addition of the short substrate oligonucleotide to report the presence of a certain miRNA in an in vivo context.…”
Section: Aptamers As Probes For Screening Approachesmentioning
confidence: 99%